2015
DOI: 10.1016/j.enconman.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Biomass as blast furnace injectant – Considering availability, pretreatment and deployment in the Swedish steel industry

Abstract: a b s t r a c tWe have investigated and modeled the injection of biomass into blast furnaces (BF), in place of pulverized coal (PC) from fossil sources. This is the easiest way to reduce CO 2 emissions, beyond efficiencyimprovements. The considered biomass is either pelletized, torrefied or pyrolyzed. It gives us three cases where we have calculated the maximum replacement ratio for each. It was found that charcoal from pyrolysis can fully replace PC, while torrefied material and pelletized wood can replace 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…Intensive work is being done to mitigate the CO 2 emissions in steel industry by partial substitution of fossil fuels (coal and coke) with renewable source of energy such as biomass. [7][8][9][10][11][12][13][14][15] One of biomass materials which could be used as binder for briquettes and reducing agent in blast furnace is lignin. Lignin is considered as the second most abundant renewable biomass on the earth after cellulose and it represents about 30% of the total raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive work is being done to mitigate the CO 2 emissions in steel industry by partial substitution of fossil fuels (coal and coke) with renewable source of energy such as biomass. [7][8][9][10][11][12][13][14][15] One of biomass materials which could be used as binder for briquettes and reducing agent in blast furnace is lignin. Lignin is considered as the second most abundant renewable biomass on the earth after cellulose and it represents about 30% of the total raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [30] injected pelletized, torrefied or pyrolyzed biomass into blast furnaces in place of pulverized coal, and noted their replacements could be up to 100%, 22.8% and 20.0%, respectively.…”
Section: Fuels Combustion and Chemical Processesmentioning
confidence: 99%
“…Coke and coal as main reducing agents in the BF are the main contributors to CO 2 emitted during iron and steel making. The European Union (EU) has set a target to cut 80% of the CO 2 of fossil carbon, by 2050 [3]. In several studies the possible decrease in fossil CO 2 emissions by using biomass is reported [4][5][6].…”
Section: Introductionmentioning
confidence: 99%